Proposing a model for absorption capacity of technology - Gholizadeh, Hossein; Bonyadi Naeini, Ali; Moini, Alireza (International Journal of Engineering and Technology, 2015)
Absorption capacity of knowledge is the concept which is been introduced in this situation. This phenomenon describes why some countries are in a better condition with a view to technology. Many countries believe that the power to stay in the battle and excel other competitors directly depends on their abilities in taking knowledge. Many countries have used their technological gap with developed countries as an accelerator for improving their absorption capacity. In this study, authors tried to produce a complete definition for absorption capacity through analyzing different research. Then with using expert opinions, a categorization for dimensions of absorption capacity will be prepared by using the structural equation modeling analysis, and finally a model for measuring absorption capacity is suggested. The results show effective dimensions in 5 different section. Studies depict that the most important one is keeping which could be a fundamental for long-term policies of 1404.